2019
DOI: 10.1371/journal.pone.0219178
|View full text |Cite
|
Sign up to set email alerts
|

Validating self-reported cervical cancer screening among women leaving jails

Abstract: Background Despite women with criminal justice involvement reporting routine Papanicolaou (Pap) testing, significant disparities in cervical cancer outcomes exist when compared to women without criminal justice involvement. A possible reason for the discrepancy is that this group of women may be misreporting Pap testing. The objective of this study was to validate self-reported cervical cancer screening among women leaving jails. Methods We used three methods to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Another limitation is that we did not collect data from medical records to confirm abnormal results or assess the severity of dysplasia. Previous studies have found a high degree of correlation between self-reported Pap data and validated test results among criminal-legal involved women [47]. Finally, the 288-item survey takes approximately 45 minutes to complete and can be burdensome for participants.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we did not collect data from medical records to confirm abnormal results or assess the severity of dysplasia. Previous studies have found a high degree of correlation between self-reported Pap data and validated test results among criminal-legal involved women [47]. Finally, the 288-item survey takes approximately 45 minutes to complete and can be burdensome for participants.…”
Section: Discussionmentioning
confidence: 99%
“…Tyler is an underserved rural area with an estimated population size of around 105,729 people [23]. Moreover, due to the lack of health literacy and related awareness, particularly among the uninsured minorities as demonstrated in other studies [24,25], limited visits could occur in the clinic for cervical health checkups. Another limitation is the lack of comprehensive follow-up data, which stemmed from the limited number of visits by the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent pilot study assessing the relationship between women’s self-reports, medical records and a cervical health literacy score found a significant association between high literacy scores and accurate self-report. [ 24 ] This pilot was an attempt to address previous criticisms that Pap tests were potentially over-reported; the addition of a cervical health literacy assessment to future research using women’s self-report of Pap testing may improve the validity of findings.…”
Section: Discussionmentioning
confidence: 99%